Comparative Analyses of 3,654 Plastid Genomes Unravel Insights Into Evolutionary Dynamics and Phylogenetic Discordance of Green Plants - Yang, Ting; Sahu, Sunil Kumar; Yang, Lingxiao; Liu, Yang; Mu, Weixue; Liu, Xin; Strube, Mikael Lenz; Liu, Huan; Zhong, Bojian (Frontiers in Plant Science, 2022)
The plastid organelle is essential for many vital cellular processes and the growth and development of plants. The availability of a large number of complete plastid genomes could be effectively utilized to understand the evolution of the plastid genomes and phylogenetic relationships among plants. We comprehensively analyzed the plastid genomes of Viridiplantae comprising 3,654 taxa from 298 families and 111 orders, and compared the genomic organizations in their plastid genomic DNA (ptDNAs) among major clades, including gene gain/loss, gene copy number, GC content, and gene blocks. We discovered that some important genes exhibiting similar functions likely formed gene blocks, such as the psb family presumably showing co-occurrence and forming gene blocks in Viridiplantae. The inverted repeats (IRs) in plastid genomes have doubled in size across land plants, and their GC content is substantially higher than non-IR genes. By employing three different data sets [all nucleotide positions (nt123), only the first and second codon positions (nt12), and amino acids (AA)], our phylogenomic analyses revealed Chlorokybales+Mesostigmatales as the earliest-branching lineage of streptophytes. Hornworts, mosses, and liverworts forming a monophylum were identified as the sister lineage of tracheophytes. Based on nt12 and AA data sets, monocots, Chloranthales and magnoliids are successive sister lineages to the eudicots + Ceratophyllales clade. The comprehensive taxon sampling and analysis of different data sets from plastid genomes recovered well-supported relationships of green plants, thereby contributing to resolving some long-standing uncertainties in the plant phylogeny.